2021
DOI: 10.4103/joco.joco_89_20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of E-Schooling on Digital Eye Strain in Coronavirus Disease Era

Abstract: Purpose: To assess digital eye strain (DES) among schoolchildren during lockdown. Methods: An online questionnaire-based, cross-sectional study was conducted. A validated, self-administered, electronic questionnaire was circulated among students of 5–18 years of age. The duration of data collection was from May 18, 2020 to May 24, 2020. Rasch-based Computer-Vision Symptom Scale was deployed to measure the DES. Results: A total of 654 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 18 publications
(23 reference statements)
1
41
0
4
Order By: Relevance
“…The reported surge in the proportion of children using DD for more than the recommended 2 h a day during the lockdown ( Mohan et al, 2021 ), was associated with an increase in the likelihood for reporting ocular complaints in this study. Considering that uncorrected refractive error or not using the prescribed correction has been linked to ocular complaints of headaches among children who used DD ( Gupta, Chauhan & Varshney, 2021 ; Portello et al, 2012 ; Vilela et al, 2015 ), the higher prevalence of ocular complaints in this study may be related to the fact that majority of the schoolchildren either did not use spectacles when working with their devices, and/or not had an eye examination in the last year.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The reported surge in the proportion of children using DD for more than the recommended 2 h a day during the lockdown ( Mohan et al, 2021 ), was associated with an increase in the likelihood for reporting ocular complaints in this study. Considering that uncorrected refractive error or not using the prescribed correction has been linked to ocular complaints of headaches among children who used DD ( Gupta, Chauhan & Varshney, 2021 ; Portello et al, 2012 ; Vilela et al, 2015 ), the higher prevalence of ocular complaints in this study may be related to the fact that majority of the schoolchildren either did not use spectacles when working with their devices, and/or not had an eye examination in the last year.…”
Section: Discussionmentioning
confidence: 89%
“…These findings are consistent with previous studies that reported a similar higher prevalence of headaches among school children who used DD ( Agarwal, Goel & Sharma, 2013 ; Dessie et al, 2018 ; Mohan et al, 2021 ; Portello et al, 2012 ; Shantakumari et al, 2014 ), and for those studies that reported lower rates of headache (ranging from 17.9–50.2%)( Bahkir & Grandee, 2020 ; Ichhpujani et al, 2019 ; Vilela et al, 2015 ), they were not conducted during the lockdown period. However, a study in India found that most of the participants experienced heaviness (79.7%) and redness of the eye (69.1%) ( Gupta, Chauhan & Varshney, 2021 ). In another study that determined the relationship between screen time (ST) and dry eye, researchers reported that eye fatigue was more prevalent than other ocular complaints in a pediatric population ( Elhusseiny et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that age and use of a digital device for more than five hours per day were the independent risk factors associated with DES [ 2 , 5 , 7 , 11 , 12 , 14 ]. These findings are also valid in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a higher prevalence of DES (92.8%) due to online classes and increased screen exposure. The most common symptoms in the study were: heaviness of eyelids and redness of the eyes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The change in sleep pattern affected the quality of sleep resulting in poor physical and mental health. Students all over the world reported physical symptoms such as eye strain and backaches due to having participated in online learning for long hours ( Ganne et al, 2021 , Gupta et al, 2021 ). The same is to be implied in Brunei.…”
Section: Mental Health Issues Brought About By E-learningmentioning
confidence: 99%